Indian perspective about COVID-19 vaccine: an elixir bringing ray of hope to the dark pandemic - Thakur, Vivek; Vanya, Vidhi; Sarkar, Avir; Mazumdar, Basanti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
India has finally begun its colossal coronavirus vaccine drive, desperately hoping to end a deadly pandemic that has killed around 1.5 lakh of its population. With an aim to vaccinate about 300 million people across the subcontinent by July, India has a huge task ahead. This large number roughly amounts to almost the entire US population.